La Liga (Ligaria cuneifolia) como recurso alimenticio clave para aves del Monte de la provincia de La Rioja - Fracchia, Gerónimo; Aranda-Rickert, Adriana (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.